PERLINDUNGAN HUKUM TERHADAP LEMBAGA PERBANKAN ATAS PENYALURAN KREDIT DENGAN JAMINAN RESI GUDANG (Studi Pada PT. Bank Pembangunan Daerah Jawa Barat dan Banten dan PT. Bank Pembangunan Daerah Jawa Tengah) - , DISA MASNASILTIE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Since the Government and the House of Representatives of Indonesia has passed Undang-undang Nomor 9 of 2006 about Warehouse Receipt System, have been emended became Undang-undang of 2011, there is a solution for agribusiness sector to get working capital from banking institution with warehouse receipt as credit guarantee. Banking institution as a intermediary institution should have to do prudential principle when providing loans. Before Undang-undang Nomor 9 of 2006 have been emended banking are generally less interested giving credit to agribusiness sector by the reason of high risk of this sector, but Undang-undang Nomor 9 Tahun 2006 provide legal protection for banking institution especially when banking channeling credit with warehouse receipt as credit guarantee. At the implementation, the problem of warehouse receipt sytem in Indonesia actualy is still in level of refinement.